IDENTIFIKASI PENGGUNAAN OBAT PADA PASIEN DIABETES MELLITUS TIPE II USIA LANJUT DENGAN BEER’S CRITERIA DI INSTALASI RAWAT INAP RUMAH SAKIT IBNU SINA MAKASSAR PERIODE TAHUN 2012 - Rizqi Nur Azizah; A. Hudayah (Fakultas Farmasi UMI, 2016)
Using identification in the use medicine with Beer's Criteria to the advanced age patients in Inpatient installation in Ibnu Sina Makassar Hospital which aims to observe, report, and identify in the use medicine in elderly patient of Type II Diabetes Mellitus are covered by Beer's Criteria in inpatient installation in Ibnu Sina Makassar Hospital period 2012. This is a descriptive research by collecting data retrospectively. The results of this research concluded in the use medicine there are 8 types of drugs covered by the Beer’s Criteria, they are alprazolam 14.28%, insulin 64.28%, gliburide (gluconic®) 1.19%, metoclopramide (sotatic®) 4.76%, Kal. Diklofenak (kataflam®) 1.19%, mefenamic acid 3.57%, meloxicam 2.38%, and ketorolak 8.33%.